Factors associated with neonatal resuscitation knowledge and comfort across academic anesthesia institutions. (18th October 2022) - Drzymalski, Dan M.; Gao, Wenxi; Moss, David R.; Liao, Benita T.; Shore-Lesserson, Linda; Podovei, Mihaela
Abstract: Background: Neonatal resuscitation training is a requirement for all obstetric anesthesia fellows. However, while the majority of anesthesiologists who work on labor and delivery report having been involved in the resuscitation of a newborn, most do not have NRP training. Objective: By studying a national cohort of anesthesiologists, our objective was to identify factors associated with knowledge and comfort with neonatal resuscitation and to inform decisions about neonatal resuscitation in obstetric anesthesia fellowship training. Materials and methods: After receiving exempt status, a survey assessing knowledge and comfort with neonatal resuscitation was sent to US academic institutions. Univariable and multiple variable regression analyses were performed to assess factors associated with knowledge and comfort. All statistical analyses were performed using R software (R version 3.4.3 [2017-11-30]; R Foundation for Statistical Computing, Vienna, Austria). Results: Responses were received from 32 (84%) of 38 academic institutions that participated. A total of 245 surveys were collected from 20 December 2018 to 27 September 2019. The mean (standard deviation (SD)) percentage of correct knowledge answers in the cohort was 43.3% (22.6%). Knowledge scores were associated with obstetric anesthesia fellowship training, regularly working with infants, and current neonatal resuscitation program (NRP) training. The mean (SD) sum of comfort ratings from the individual questions was 49.9 (17.9). Comfort ratings were associated with pediatric anesthesia fellowship training, regularly working with infants, current NRP training, and having at least one year of general pediatrics residency training. Conclusions: Obstetric anesthesiologists have the knowledge but appear to lack the comfort to perform neonatal resuscitation. As obstetric anesthesiologists are sometimes involved in neonatal resuscitation, maintenance of certification is important in maintaining comfort with neonatal resuscitation if not regularly working with infants.